總體經濟因素與資訊傳遞效果於美國與台灣債券市場動態過程之研究 - 王凱立; 林卓民; 王美智; Kai-Li Wang; Cho-Min Lin; Mei-Chih Wang (My University, 2010)
本文提出一般化TCC MGARCH-MSKST模型，針對美國與台灣債市價格發現與訊息傳遞機制，考量美、台債市跨市場報酬及波動傳導、自身市場及跨市場之波動不對稱傳導、總體經濟因素對於債市報酬與波動之解釋能力、自身市場與跨市場風險溢酬、不同型態貨幣政策宣告對於債市價格變動的不對稱反應及不同貨幣政策結構下對於報酬、波動、訊息流動與共變異結構影響等因素，據以提供美、台債市動態行爲更深入的分析。實證結果顯示，美債不論報酬或波動對台債皆具領先效果，且美債對台債訊息傳遞主要經由不對稱波動傳導途徑進行。總體經濟變數部分，包括貨幣政策宣告、股市、利率及匯率，對於債市價格及波動過程存在一定程度解釋能力。其次，針對央行貨幣宣告事件，發現美國聯準會貨幣政策宣告造成之市場波動持續，比其他型態訊息衝擊短暫，以較快速度被市場吸納而弱化波動行程。本文發現美債相對台債快速消化市場干擾，以較短時程調整回復至穩定水準，因而降低市場波動的持續性。最後，檢驗美債和台債相關係數，發現美、台債市呈現顯著正相關，且美國聯準會重大貨幣政策宣告明顯增加跨國債市同期關聯，說明美、台債市同期連動存在隨時間門檻轉換性質。

This paper proposes a general TCC MGARCH-MSKST model to investigate the dynamic relationship between U.S. and Taiwan bond markets. We analyze the price discovery and information transmissions mechanism in two markets, bringing monetary announcement effects and macroeconomic factors into considerations. Our empirical evidences reveal there is return and volatility spillover effects from U.S. to Taiwan bond markets; moreover the information transmission primarily follow asymmetric volatility spillover path. Regarding the macroeconomic variables, we found monetary policy announcements, stock, interest rate and exchange rate offer some extent explanatory power for pricing and volatility in bond markets. We also discover Fed monetary announcement shock will absorb quickly by the market, leading to volatility persistence of brief duration in comparisons to other types of information shock. Finally, in our examination these two markets exhibit a significant positive correlation coefficient. Fed monetary announcements clearly increase the contemporaneous correlation in these two markets, implying the correlation in two markets exhibit time varying threshold properties.
Macroeconomic News and Information Transmission of Bond Markets between U.S. and Taiwan
Keywords: 債券市場; GARCH模型; 波動; 風險; 訊息傳導; 貨幣政策宣告; Bond Market; GARCH; Volatility; Risk; Information Transmission; Monetary Policy Announcements